Hybrid Parallel Multithreading Encryption - Deepali; Kakkar, Namita (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is a new area for the field of research. In the current scenario the server and client architecture is advanced giving rise to speed and reliability and is been shifting from distributed or cluster to cloud architecture since cloud architecture maintains the server in various number of features. The main part of this research relies on a robust architecture which deals with Cloud Storage as a Service (SAAS) and comparative security measures of improvement and modifications. Various security measures have been studied during this research which is briefly described in various sections of this report. The main motive of shifting the platform to cloud is its “popularity” and “portability”. Smart phone devices are booming in market and it covers most of the works of people which was earlier used to done by the help of computer. We can read mails with push notifications facility, we can communicate and store large number of data in mobile devices thus the technology is shifting from distributed to cloud platform. Client Server Architecture- this method is a first part of study of this thesis which was needed to be developed before moving onto the next levels of Cloud Computing. The client section was a simple application for user which was made on Socket Programming in Java. Application connection was made with Server which is a LAN based server on which data is to be uploaded and downloaded. Analyzing RSA and NTRU in parallel computing environment is developed, then it needs to be secured with a particular algorithm or technique. The algorithm studied is known as RSA key oriented algorithm which offers dynamic security on client and server level during communication. The other technique for advancing the level of scalability and improvement alone the network layer we used is NTRU encryption.